2021
DOI: 10.1186/s13148-021-01068-8
|View full text |Cite
|
Sign up to set email alerts
|

HDAC2 enhances esophageal squamous cell carcinoma development through down-regulating microRNA-503-5p and promoting CXCL10

Abstract: Objective Although esophageal squamous cell carcinoma (ESCC)-oriented mechanism has been widely explored, the integrated action of histone deacetylase 2 (HDAC2), microRNA (miR)-503-5p and C-X-C motif chemokine 10 (CXCL10) in ESCC has not been thoroughly explored. Thus, we performed the research to study the role of HDAC2/miR-503-5p/CXCL10 axis in ESCC. Methods ESCC tissues and mucosal tissues (5 cm from cancer tissues) were collected, in which HDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…EEF1E1A is a novel LIHC prognosis predictor and associated with immune infiltration ( 59 ). A recent study showed that HDAC2 can bind to miR-503-5p and target CXCL10 , thus promoting the progression of esophageal squamous cell carcinoma ( 60 ). These hub genes were further shown to correlate positively with the PI3K/AKT/mTOR signal pathway molecules.…”
Section: Discussionmentioning
confidence: 99%
“…EEF1E1A is a novel LIHC prognosis predictor and associated with immune infiltration ( 59 ). A recent study showed that HDAC2 can bind to miR-503-5p and target CXCL10 , thus promoting the progression of esophageal squamous cell carcinoma ( 60 ). These hub genes were further shown to correlate positively with the PI3K/AKT/mTOR signal pathway molecules.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with the conclusions from recent studies that HDAC acts as a regulator in tumor via changing the nucleosome conformation of tumor cells. It is well acknowledged that HADC participates in cellular modulation in various cells by regulating miRNAs, for example, HDAC2 regulates miR-503-5p in esophageal squamous cell carcinoma [ 35 ], HDAC2 promotes the endothelial dysfunction induced by diabetes [ 36 , 37 ], and HDACs regulate the cellular differentiation in neurodegenerative diseases [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…HDAC2 bound to the promoter sequences of miR-503–5p. and miR-503–5p suppressed the proliferation of ESCC cells both in vitro and in vivo [90] .…”
Section: The Molecular Network Of Hdac2 and Mirnasmentioning
confidence: 94%
“…The inhibition of HDAC decreased CCAAT/enhancer-binding protein α mRNA expression in HCC cells by inducing miR-124–3p and miR-25 expression [89] . HDAC2 was upregulated, and miR-503–5p was down-regulated in ESCC [90] . HDAC2 bound to the promoter sequences of miR-503–5p.…”
Section: The Molecular Network Of Hdac2 and Mirnasmentioning
confidence: 96%